2017
DOI: 10.2334/josnusd.16-0722
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of oral microbiota in elderly nursing home residents with diabetes

Abstract: Over 700 bacterial species have been detected in the oral cavity. Several studies have suggested that periodontitis is associated with systemic disorders such as diabetes mellitus, indicating a key role for oral microbiota in human health. However, the relationship between oral microbiota and diabetes has not been well clarified. Therefore, we conducted microbiome analysis of saliva samples obtained from 15 elderly residents (3 with type 2 diabetes mellitus [DM] and 12 without diabetes [non-DM]) at three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
7
26
0
Order By: Relevance
“…Emerging data derived from high-throughput metagenomic sequencing of the oral microbiome with 16S rDNA or rRNA support the role of these microorganisms in the development of DM, but the findings remain controversial (Long et al 2017;Ogawa et al 2017;Tam et al 2018;Saeb et al 2019). Similar to our findings, these studies showed differences between glycemic statuses and the proportions of several phyla.…”
Section: Discussionsupporting
confidence: 83%
“…Emerging data derived from high-throughput metagenomic sequencing of the oral microbiome with 16S rDNA or rRNA support the role of these microorganisms in the development of DM, but the findings remain controversial (Long et al 2017;Ogawa et al 2017;Tam et al 2018;Saeb et al 2019). Similar to our findings, these studies showed differences between glycemic statuses and the proportions of several phyla.…”
Section: Discussionsupporting
confidence: 83%
“…A study of supragingival plaque, as well as tongue scrapings and saliva samples used metagenomics and 16S rRNA sequencing for a more comprehensive characterization of the oral microbiome . However, due to ease of sampling, salivary samples provide a distinctive advantage for screening purposes and have been used in various studies of health and disease . In addition to sampling, the choice of hypervariable regions of the 16S rRNA gene that have been sequenced have an impact on characterizing the diversity of the oral microbiome .…”
Section: Discussionmentioning
confidence: 99%
“…42 However, due to ease of sampling, salivary samples provide a distinctive advantage for screening purposes and have been used in various studies of health and disease. 10,16,[43][44][45][46][47] In addition to sampling, the choice of hypervariable regions of the 16S rRNA gene that have been sequenced have an impact on characterizing the diversity of the oral microbiome. 31 Another potential limitation is lack of sample replicates within our study design and thus we are not able to assess individual variability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared SM in patients with diabetes to that of healthy controls by means of NGS, and in general, data show that diabetes associates with a decrease in bacterial diversity of SM [66][67][68]. In addition, higher salivary levels of P. gingivalis, T. forsythia and F. alocis were reported in patients with gestational diabetes [69], whereas only minor differences were identified in children with T2DM, when compared to obese and healthy controls, respectively [70].…”
Section: Diabetes and Obesitymentioning
confidence: 99%